A quantitative content analysis of the characteristics of rapid-growth firms and their founders - Barringer, Bruce R.; Jones, Foard F.; Neubaum, Donald O. (Journal of Business Venturing, 2005)
A group of firms that is attracting attention are rapid-growth firms. These firms are of particular interest because rapid growth is an indication of market acceptance and firm success. By studying rapid-growth firms, researchers can help all firms better understand the attributes associated with firm growth. Despite these positive outcomes, however, rapid firm growth is difficult to achieve and maintain. This study adds to the literature through a quantitative content analysis of the narrative descriptions of 50 rapid-growth firms and a comparison group of 50 slow-growth companies. The purpose of the study was to draw from the narratives a list of empirically grounded growth-related attributes that are associated with rapid-growth firms. The findings of the study resulted in the advancement of a conceptual model of the attributes of rapid-growth firms in four areas: founder characteristics, firm attributes, business practices, and human resource management (HRM) practices.